Research into Spinal Deformities 1 - Sevastik, J.A. (IOS Press, 2014)
In this book the results of current multidisciplinary research on different aspects of spine deformities as the etiology, the pathogenesis, the pathomechanism, the three-dimensional imaging of the spine and back, the biomechanics and kinematics of the normal and deformed spine, as well as the conservative and surgical treatment of these conditions are presented by world's most prominent researchers in the different fields of the topic